Do There Any Higher Order Thinking Skills in the Cambridge Primary Mathematics Textbook? (Universitas Negeri Semarang, 2022)
The poor results of national and international assessments make the national curriculum get criticism. Meanwhile, the Cambridge curriculum gets popular because of its quality. Textbooks as curriculum manifestations affect student learning. This study describes Higher Order Thinking Skills (HOTS) and the dominance of its level in the Cambridge Primary Mathematics 4 textbooks which are Teacher's Resources and Learner's Book. This study uses a directed qualitative content analysis method. This research shows that all HOTS levels (analyze, evaluate, and create) are spread across four major themes (number, measure, data handling, and geometry) Teacher's Resource and Learner's Book. Theoretically, HOTS in the Teacher's Resource and Learner's Book can teach critical thinking, creativity, collaboration, and communication because the learning content of HOTS in this book uses a student-centered approach and the teacher actively provides scaffolding using open-ended questions, discussions, and group activities. HOTS level creating is dominant in Teacher's Resource and analysis is dominant in Learner's Book. Abstrak Hasil assesmen nasional dan internasional yang konsisten buruk membuat kurikulum nasional menuai kritik. Sementara itu, kurikulum Cambridge diminati sejumlah kalangan karena dianggap lebih berkualitas. Buku teks sebagai manifestasi kurikulum berpengaruh terhadap pembelajaran siswa. Tujuan penelitian ini yaitu mendeskripsikan Higher Order Thinking Skills (HOTS) dan dominasi levelnya dalam buku teks Cambridge Primary Mathematics 4 yang terdiri dari Teacher’s Resources dan Learner’s Book. Penelitian ini menggunakan metode analisis isi kualitatif terarah. Hasil penelitian ini menunjukkan bahwa ketiga level HOTS (menganalisis, mengevaluasi, dan mencipta) tersebar dalam keempat tema besar (number, measure, handling data, dan geometry) Teacher’s Resource dan Learner’s Book. Secara teoretis, HOTS dalam Teacher’s Resource dan Learner’s Book dapat membelajarkan critical thinking, creativity, collaboration, dan communication karena pembelajaran muatan HOTS dalam buku ini terpusat pada siswa dan guru aktif memberikan scaffolding menggunakan pertanyaan open-ended, diskusi, serta aktivitas berkelompok. HOTS dalam Teacher’s Resource didominasi oleh level mencipta, sedangkan Learner’s Book didominasi level menganalisis.